The Reality of the Sacred in Mircea Eliade’s Phenomenology of Religion - Sully, Elmi Hamidah; Arifuddin, Nawawi Bahar; Truna, Dody S.; Rosyad, Rifki (MSJ : Majority Science Journal, 2026)
Mircea Eliade was a Romanian historian of religion and philosopher from Bucharest. He became influential in religious studies during the 20th century, focusing on the importance of myths and symbols in human experience. Notable works include "The Sacred and the Profane" and "Patterns in Comparative Religion," where he explored personal spiritual experiences and the distinction between the sacred and the profane. Eliade introduced concepts such as hierophanies, which refer to the manifestation of the sacred in everyday life. His scholarship laid the groundwork for comparative religion studies and enriched contemporary discussions on religious theories. His work laid the foundation for comparative religion studies and provided critical insights that inform contemporary discussions of the theories of religion. Scholars have drawn on his concepts to explore themes such as ritual, symbolism, and the human quest for meaning, thereby shaping various theories in the field. Eliade's legacy continues to inform how we study and interpret religions today. This research aimed to explore Eliade’s perspective on the interpretation of sacred knowledge in religion and beyond. Mircea Eliade’s "The Reality of the Sacred" is significant for several reasons, including the distinction between the sacred and the profane, the importance of myth and symbols, and the concept of Hierophanies. Overall, "The Reality of the Sacred" is celebrated for its innovative ideas and profound implications for understanding the nature of religious experience, positioning Eliade as one of the most influential figures in the study of religion. While his legacy continues to shape contemporary discussions in the field, it is essential to acknowledge certain aspects that might be lacking. Additionally, some criticisms of his writing merit further exploration.